PERSEPSI PRIA TERHADAP WANITA KARIR DI PEKANBARU (Studi Pada Pegawai PT. BNI (Persero) Tbk Kantor Cabang Pembantu Tangkerang) - ", Wahyudi; Wirman, Welly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Working is one way to earn money in order to meet the various needs of life and hope that work activities will bring them to satisfying condition. Nowadays, at the age of emancipation of women, working is not only done by men. Women also had a space in the public community, even companies have provided a special position that is filled by women. One company that provides positions for women is PT. BNI (Persero) Tbk Branch Office Subsidiary Tangkerang in Pekanbaru, where the front line is the majority position filled by women. As individuals who have multiple roles, women are required to be aligned as a woman it self and also as a career woman in her profession. Multi role that owned by women raises the perception for men. Although the reality of a career woman can be seen and felt by the public at this time, but the stigma attached to women who says women should take care of the family and raising their kids still become a tradition of the society. This research aims to determine how perceptions of male to female careers in Pekanbaru (Research on Employee PT. BNI (Persero) Tbk Branch Office Subsidiary Tangkerang).The method are used in this research is Descriptive Qualitative method. Informants in this research consists of four people and data collection techniques are grouped into three sections, which are: in-depth interviews, observation, and documentation. This research is using data analysis interactive model of Miles and Hubermen, that checks the validity of the data through the extension of participation and triangulation.The result of this research indicates that employee perception of men toward female employees at PT. BNI (Persero) Tbk Branch Office Subsidiary Tangkerang Pekanbaru are the perception of positive and negative perceptions. The response to female employees is positive, because of male employees are attracted by their physical appearance. Career woman personally considered by four informants as independent, strong and ambitious woman that doing some exclusion of other priorities in life. Reaction toward career woman in the form of interaction and daily activities. Relation between them is not limited about professional occasion, but also their individual relationship.Key Word : Perception, Female Career